Monitoring of fin-fish resources from Uran coast (Raigad), Navi Mumbai, Maharashtra, West coast of India - Pawar*, Prabhakar R. (International Multidisciplinary Research Journal, 2011)
India is rich in natural resources and the annual harvestable fishery potential of the country is estimated to be 3.48 million tones. It is established that the fish biodiversity of the country is diminishing at an alarming rate in all the aquatic zones. The data on species diversity of fishes from Uran coast revealed presence of 31 species of which 3 species of Chondricthyes representing 2 genera and 2 families and 28 species of Osteicthyes representing 28 genera and 23 families were recorded. Of the recorded species, 55 % belonged to Order Perciformes, 10 % to Clupeiformes, 6 % each to Rajiformes, Mugiliformes and Ã‚Â Anguilliformes, 3 % each to Aulopiformes, Carcharhiniformes, Pleuronectiformes, Ã‚Â Siluriformes and Tetraodontiformes. Among the recorded species, ribbon fishes/spiny hair tail (Lepturacanthus savala), croakers (Johnius soldado), dhoma (Sciaena dussumierii) and gold spotted grenadier anchovy (Coilia dussumierii) are abundant where asÃ‚Â BleekerÃ¢â‚¬â„¢s whipray (Himantura bleekeri), Sharp nose stingray (H. gerrardi) and Spotted Green Puffer fish (Tetraodon nigroviridis) were rare. Stripped mullet (Mugil cephalus), cat fish (Mystus seenghala), three stripped tiger fish (Terapon jarbua) and mudskippers (Boleophthalmus boddarti) were very common. At present, the yield of fin-fish resources from Uran coast is optimum; it is decreasing day by day due to coastal pollution affecting the status of the local fishermen because of which they are looking for other jobs for their livelihood.